Design of a Multivariable Nonlinear Control System based on the State Feedback Linearization Method applied to a Dof Spherical Manipulator Robot - Maravi Pinto, Ronald Divio (2001)
This paper presents the multivariable feedback linearization methodology applied to a spherical robot arm of 2 DOF to solve the problem of trajectory tracking. The base of the robot arm (a metallic disk joined to a metallic bar) is driven by a first DC motor, while its metallic link is driven by a second DC motor. Both motors possess optical encoders to sense angular positions.The robot arm is a multivariable square process with two inputs (armature voltages) and two outputs (angular positions of the base and the link). Simulation results of the designed nonlinear control system will demonstrate that the designed control inputs make the outputs capable of tracking desired trajectories.